Pengaruh Citra Merek Honda Terhadap Kepuasan Konsumen (Survey Pengguna Motor Matic Honda Di Kota Tangerang) - Fitri Sari; Putri Adinda Lelono; Ragiliza Septyacahyaning; Syakira Dwi Andani (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The global automotive industry is a dynamic economic sector that continues to develop and faces intense competition. Over the past few decades, Honda has grown significantly and become one of the major players in this business. One of the main reasons for Honda's success is its ability to build a tight brand identity. The focus of this research is to explain the influence of Honda's brand image on consumer satisfaction. The theory used is the uses and effect theory with quantitative research methods. This research uses a descriptive approach. The objects taken in this research were Honda automatic motorbike users in Tangerang City. This research used a non-probability sampling technique with an accidental sampling method with a sample of 100 respondents. The paradigm used is the positivism paradigm. The data analysis techniques used are normality test techniques, heteroscedasticity tests, simple linear regression analysis tests, and hypothesis testing with the SPSS 27 application. The results of this research have a positive influence between the variable Brand Image (X) and the variable Consumer Satisfaction (Y). Thus, the brand image variable has a proportional influence on consumer satisfaction of 60.9%.